A summary of the osteosarcoma banking efforts: A report from the Children's Oncology Group and the QuadW Foundation. Issue 3 (8th December 2014) - Glover, Jason; Krailo, Mark; Tello, Tanya; Marina, Neyssa; Janeway, Katherine; Barkauskas, Don; Fan, Timothy M.; Gorlick, Richard; Khanna, Chand; the COG Osteosarcoma Biology Group
<x xml:space="preserve">Abstract</x> Background Survival rates of patients with osteosarcoma have remained stagnant over the last thirty years. Better understanding of biology, new therapeutics, and improved biomarkers are needed. The Children's Oncology Group (COG) addressed this need by developing one of the largest osteosarcoma biorepositories ever, containing over 15, 000 tumor and tissue samples from over 1, 500 patients. Procedure The biology study P9851 and the banking study AOST06B1 has enrolled 1, 787 patients (as of September, 2013). Clinical information was lacking on 510 patients on P9851, who were not enrolled on a concurrent therapeutic trial. The value of these specimens was diminished. The lack of statistical support available for biology projects slowed the analysis of several critical studies. The QuadW Foundation, CureSearch, and the COG formed the Childhood Sarcoma Biostatistics and Annotation Office (CSBAO) to provide the infrastructure and address these needs by linking clinically annotated patient data to archived tissue samples and to develop biostatistical support for childhood sarcoma research. Results Originally 5.3% of samples from the 510 patients on P9851 not enrolled on a therapeutic study had full clinical annotation. The efforts of the CSBAO have linked clinical annotation to 90.8% of those specimens and provided statistical analyses to several studies that had used COG samples. As a result, 24 biology studies in osteosarcoma have been completed and published in peer‐reviewed journals. Conclusions These samples and in‐silico data are available to the research community for basic and translational science projects to improve the biological understanding and treatment of patients affected by osteosarcoma. Pediatr Blood Cancer 2015;62:450–455. © 2014 Wiley Periodicals, Inc.